EFFECTIVENESS OF FINANCIAL PERFORMANCE OF PROVINCIAL GOVERNMENTS IN INDONESIA: EVIDENCE DURING COVID-19 - Agustina, Dila Salsa; Dwi Urip Wardoyo (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
The nominal number of cases of inefficiency, inefficiency, and ineffectiveness shows a significant increase, reflecting the government's financial performance in managing finances. This research aims to analyze the financial performance of provincial governments in Indonesia, which is measured through indicators of capital expenditure, local revenue, and balancing funds in the initial period of COVID-19 (2019-2020) and the transition period of COVID-19 (2021-2022). 133 local government budget realization reports in Indonesia were analyzed using panel data regression. The research results show that local revenue significantly affected the local government's financial performance in these two periods. However, balancing funds only had a substantial impact during the early period of COVID-19. Capital expenditures negatively and insignificantly affect financial performance during the initial and transition periods. The results of this research provide an overview of the impact of COVID-19 on the financial performance of provincial and regional governments in Indonesia.